The Urgence of Enforcement of Administrative Law on the Implementation of Taxation in the Context of Welfare State Countries during the Covid-19 Pandemic - Dina Aryanti; Nuria Enggarani (Universitas Muhammadiyah Surakarta, 2022)
Administrative violations at the KPP Pratama Surakarta during the Covid-19 pandemic experienced an increase, so to overcome these problems it was necessary to enforce administrative law enforcement by implementing administrative sanctions in the taxation sector. This is due to reduce non-compliant behavior of taxpayers, as well as provide protection and certainty for taxpayers where the collected tax funds will be used to realize people's welfare. This research is a normative-empirical legal research using the legal approach and thesociologyof law. This study uses primary and secondary data. Then the data obtained is processed and analyzed by analyzing the data qualitatively. The results of this study indicate that the application of administrative sanctions during the Covid-19 pandemic at KPP Pratama Surakarta is the last solution in enforcing administrative law and has been applied according to the applicable tax regulations. And the urgency of the enforcement of administrative law on the application of taxation in the context of the welfare state during the Covid-19 pandemic at KPP Pratama Surakarta, namely if the compliance of both formal and material taxpayers is met, the collected tax funds will be used to realize the welfare of the people.